2019
DOI: 10.1556/2066.2.2019.004
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood of healthy eating among adolescents based on the health belief model

Abstract: Introduction Maintaining appropriate eating habits is one of the key components of good health. It is especially difficult during adolescence, a critical period in life because of the increased autonomy and the intention to take risks. Investigating the theoretical background of adolescents’ eating behaviour is therefore a worthwhile line of research. We applied the widely used health belief model to explore adolescents’ likelihood of healthy eating. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
3
0
1
Order By: Relevance
“…23 This could encourage a person to avoid unhealthy behaviors associated with unreadiness, inconvenience, expenditures, and difficulties. 23 Our findings are in line with previous studies, which revealed that perceived barriers had a negative DE on health-promoting behavior (B = −1.28; β = −0.13), 27,28 the likelihood of healthy eating (β = −0.31), 29 and blood pressure controlling behavior (β = −0.49). 30 This study also revealed a mediating role of perceived barriers between perceived self-efficacy and health-promoting lifestyle.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…23 This could encourage a person to avoid unhealthy behaviors associated with unreadiness, inconvenience, expenditures, and difficulties. 23 Our findings are in line with previous studies, which revealed that perceived barriers had a negative DE on health-promoting behavior (B = −1.28; β = −0.13), 27,28 the likelihood of healthy eating (β = −0.31), 29 and blood pressure controlling behavior (β = −0.49). 30 This study also revealed a mediating role of perceived barriers between perceived self-efficacy and health-promoting lifestyle.…”
Section: Discussionsupporting
confidence: 90%
“…30 Moreover, perceived benefits of healthy eating had a positive indirect influence through perceived self-efficacy. 29 Perceived selfefficacy is a psychosocial factor, in which a person is determined to modify or maintain their health-promoting behaviors. 33 Similarly, another study in the other population found perceived self-efficacy's direct and positive influence on health-promoting behaviors (β = 0.38), 34 self-management behaviors (β = 0.26), 34 and the likelihood of healthy eating (β = 0.37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adanya peningkatan persepsi risiko, keparahan, dan manfaat tersebut diharapkan dapat meningkatkan motivasi peserta untuk menjalani pola makan sehat. Individu yang memiliki perasaan rentan atau ancaman terhadap suatu risiko penyakit cenderung memiliki kesiapan dan motivasi untuk mengubah perilaku hidupnya menjadi lebih sehat (Szabo & Piko, 2019). Individu dengan persepsi ancaman dan manfaat yang tinggi cenderung memiliki niat yang besar untuk melakukan manajemen berat badan (Saghafi-Asl et al, 2020).…”
Section: Health Belief Modelunclassified
“…HBM primarily examines why individuals are willing to prevent diseases or control health conditions by extending the use of psychosocial variables (Shang et al, 2021). This model has been applied to a wide variety of healthcare behavior such as diet (Szabó and Pikó, 2019), exercise (Sas-Nowosielski et al, 2016), preventative behavior (Gever et al, 2021;Zampetakis and Melas, 2021), contraceptive use (Zhao et al, 2012), food handling (Wang et al, 2021), childbirth delivery mode (Loke et al, 2015), mental illness and depression (Castonguay et al, 2016;Nobiling and Maykrantz, 2017); and beyond related to information systems such as computer security behavior (Claar, 2011;Ng et al, 2009); online safety behavior (Abkooh, 2016); cyber-victimization preventive behavior (Dodel and Mesch, 2017). Drawing upon this model, Li (n.d.) examined university students' weight control information seeking and acceptance behavior on the Internet, while Shang et al (2021) understood the older adults' intention to share health information on social media.…”
Section: The Health Belief Model (Hbm)mentioning
confidence: 99%